Effect of isotretinoin treatment on inflammatory and hematological parameters in patients with acne vulgaris - Esen, Mustafa (Taylor & Francis Ltd, 2024)
Purpose: Although the inflammatory and anti-inflammatory effects of isotretinoin (ISO) treatment in patients with acne vulgaris have been discussed in the literature in recent years, no sensitive and specific marker has been found in studies so far. Neutrophil/HDL (high-density lipoprotein) (NHR), lymphocyte/HD L(LHR), platelet/HDL (PHR), and lymphocyte/monocyte (LMR) are new biomarkers related to inflammation. Triglyceride/HDL (TG/HDL), LDL/HDL, and total cholesterol/HDL have been shown to be cardiometabolic risk factors predicting both cardiovascular disease risk and metabolic risk, rather than just a simple dyslipidemia scale. To our knowledge, the relationship between these parameters and ISO treatment has never been studied before. We aimed to evaluate the immuno-inflammatory response of ISO treatment in patients with acne vulgaris with NHR, LHR, PHR, LMR, TG/HDL, LDL/HDL, and total cholesterol/HDL parameters.Materials and methods: In this study, 153 patients who received oral ISO treatment for at least 3 months with a diagnosis of moderate-severe acne vulgaris were evaluated retrospectively. Patients were given oral isotretinoin at a dose of 0.5-1 mg/kg. Pre and post-treatment leukocyte (WBC), neutrophil (NE), lymphocyte (LY), platelet (PLT), red cell distribution width (RDW), plateletcrit (PCT), neutrophil/lymphocyte (NLR), platelet/lymphocyte (PLR), mean platelet volume (MPV), monocyte/lymphocyte (MLR), LMR, total cholesterol, LDL cholesterol, HDL cholesterol, triglyceride, MHR, NHR, LHR, PHR, TG/HDL, total cholesterol/HDL, LDL/HDL parameters were evaluated.Results: It was found that post-treatment WBC and MPV values increased statistically significantly; NLR, neutrophil, and PCT values, on the other hand, decreased significantly (p < 0.05). No statistically significant change was detected in PLR, MLR, LMR, MHR, NHR, LHR, PHR, lymphocyte, monocyte, platelet, and RDW parameters (p > 0.05). It was determined that post-treatment total cholesterol, triglyceride, VLDL, and LDL levels increased statistically significantly; however, the HDL level decreased significantly (p < 0.05). Levels of total cholesterol/HDL, TG/HDL, and LDL/HDL were also found to increase statistically significantly (p < 0.05).Conclusion: Our study suggests that the MPV and NLR ratio as biomarkers can be used as indicators of atherosclerosis-related inflammation due to ISO treatment, but the MHR, NHR, LHR, PHR, MLR, LMR ratios cannot be used. Moreover, we believe that the ratios of TG/HDL, LDL/HDL, and total cholesterol/HDL offer a new contribution as indicators of cardiovascular risk and systemic inflammation related to ISO treatment.
Keywords: Acne vulgaris; isotretinoin; neutrophil/HDL; total cholesterol/HDL